Upaya Kepala Sekolah Dalam Meningkatkan Kompetensi Sosial Guru Di Paud Aisyah Pondok Kelapa - Yani, Yulian Handa; Margaretha, Lydia; Haryono, Mimpira (Early Childhood Research and Practice, 2025)
The purpose of this study is to examine the efforts of the principal in improving the social skills of teachers at Aisyah Early Childhood Education Centre. The type of research used in this study is descriptive qualitative research. The data collection methods used are interviews, observation, and documentation. The data sources are the teachers and principal at PAUD Aisyah Pondok Kelapa, and documentation in the form of photos taken during interviews with the teachers and principal. Data reduction involves recording the results of interviews with the teachers and principal, coding the data according to the information provided by the informants, and displaying the data by analysing the results of interviews with the teachers and principal. and data verification, which involved rethinking the interview results, reviewing field notes, rethinking the observation data and field findings, in order to draw conclusions from the research conducted. The results of this study describe the efforts of the school principal in improving the social skills of teachers at PAUD Aisyah Pondok Kelapa in Bengkulu Tengah District by involving teachers in training, workshops, seminars, and workshops to enhance their social competencies. As explained by one teacher, every teacher is always given the opportunity to participate in seminars, workshops, or training sessions organised by the government or other organisations, both offline and online.